Necesidades sociales de las personas con discapacidad en edad escolar y sus familias - Mercado García, Esther; García Vicente, Luis Mariano (Cuadernos de Trabajo Social, 2010)
Considering the importance of the family to development of certain situations, especially people with disabilities, we propose to present a qualitative study about the social and family needs, which have children with disabilities at school age; considering systemic macro and micro factors that influence to achieve an independent life. This paper, analyzes some aspects of impact of birth, social support and consequences and future of people with disabilities and their families, as well as, information and sensitization to be made by public authorities.